+0

# cuanto es 2 + 2

0
63
3

cuanto es 2 + 2

Guest 28-ago-2014
Ordenar:

#1
0

la respuesta es sencilla:

M(A,Z)c² + Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d -M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d M(A,Z)c² = Nmnc² + Zmpc² - uvA + ur(N - Z)²A-1 + ucZ²A-1/3 + usA2/3 + d =4

la respusta es: 4=a pez

#2
0

TOTALMENTE DE ACUERDO